Nontrivial Solutions of the Kirchhoff-Type Fractional p-Laplacian Dirichlet Problem. (20th June 2020) - Chen, Taiyong; Liu, Wenbin; Jin, Hua
Abstract : In this article, we consider the new results for the Kirchhoff-type p -Laplacian Dirichlet problem containing the Riemann-Liouville fractional derivative operators. By using the mountain pass theorem and the genus properties in the critical point theory, we get some new results on the existence and multiplicity of nontrivial weak solutions for such Dirichlet problem.